A Legal Framework for the Protection of Consumer Rights in E-Commerce Transactions - Handry; Wiwik Sri Widiarti; Paltiada Saragi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Consumer protection in e-commerce transactions has become an essential issue in Indonesia, with the rapid growth of digital commerce creating both opportunities and risks for consumers. The urgency of this topic stems from the challenges consumers face in exercising their rights within the digital marketplace, where laws like the Consumer Protection Law and the ITE Law often fail to ensure effective legal protection. This research aims to explore the factors that influence the effectiveness of these legal protections in e-commerce transactions and to propose recommendations for improving the legal framework. The research method used is a qualitative approach with a case study method. Data were collected through in-depth interviews, field observations, and document analysis. The study examines the implementation of consumer protection laws in the context of large and small e-commerce platforms in Indonesia. The findings of the study indicate that while legal frameworks exist, enforcement remains inconsistent, with varying levels of compliance across platforms. The research recommends strengthening the legal structure by improving consumer education, enhancing dispute resolution mechanisms, and ensuring stricter enforcement to protect consumer rights more effectively in the growing digital market. Keywords: Consumer Protection, E-commerce, Legal Framework, Indonesia, Consumer Rights.